Weight-Bearing Radiographic Analysis of the Tibiofibular Syndesmosis. Issue 3 (June 2019) - Amin, Arsalan; Janney, Cory; Sheu, Christopher; Jupiter, Daniel C.; Panchbhavi, Vinod K.
Background: Diagnosis of distal tibiofibular syndesmotic injuries includes assessment of radiographs; however, there exist no agreed on standard diagnostic criteria. Previous studies lack consistency with radiographic evaluation methods. The dynamic nature of the ankle joint supports analyzing anatomical parameters using weight-bearing films to assess for tibiofibular syndesmotic integrity. Methods: Weight-bearing tibiofibular syndesmosis radiographs of 39 male and 40 female patients were retrospectively analyzed by 3 investigators, at different levels of orthopaedic training. Measurements 1 cm above the tibial plafond for the anterior tibiofibular overlap (TFO) and tibiofibular clear space (TCS) were recorded and standardized by the fibular width (FW) at 2 time points. Data were compared to check for agreement between the sets of measurements for each rater and agreement between investigators, and to ascertain underlying gender differences. Results: There was good intraobserver correlation (intraclass correlation coefficient [ICC] > 0.90) among investigators for each parameter. A significant difference in the TFO was noted between genders (P < .05). We establish the following radiographic (anteroposterior view) parameters for an intact syndesmosis: male patients, TCS <4.57 mm or TCS/FW <29% and TFO >9.29 mm or TFO/FW > 57%; female patients, TCS <4.28 mm or TCS/FW <30% and TFO >7.41 mm or TFO/FW >51%. Conclusions: Our study provides a more objective approach by utilizing weight-bearing radiographs and performing all measurements 1 cm above the tibial plafond. Levels of Evidence : Level IV